EFFECT OF STIFFENER VARIATION ON THE FLEXURAL CAPACITYOF CASTELLATED BEAM HEXAGONAL OPENING - Ahmad Jimmy; Ida Barkiah (CERUCUK, 2022)
One of the innovations that could be done is to change the WF steel profile into a castellated beam with hexagonal openings. This research examines the effect of adding stiffener variations on castellated beams with hexagonal openings on flexural capacity. The steel profile used is a WF 150x75x5x7 steel profile with BJ 37 which is made into a castellated beam with hexagonal openings with an opening angle of 45° and a profile cut width of 50 mm with a beam length of 2000 mm with variations of stiffeners are plate 35x6, reinforcement Ø-16, and elbows. 25.25.4 with variations in distance of 200 mm and 400 mm. The analysis in this study uses manual analysis and numerical testing using the software. From the results obtained from the analysis, the flexural capacity, deformation, stress, and failure patterns that occur with each model will be compared. Based on the research results, it was found that the capacity of all models using stiffeners was greater than that of castellated steel beams without stiffeners. The reinforcement with a distance of 200 mm is the largest stiffener that can withstand the load with an increase of 6.25%.